Relationship between SARS-COV-2 And autoimmune neurological diseases - A. I. Vlasenko; O. A. Portik; G. N. Bisaga; M. P. Topuzova; V. A. Malko; P. Sh. Isabekova; N. V. Skripchenko; T. M. Alekseeva (Журнал инфектологии, 2022)
Since the onset of the SARS-CoV-2 infection, there has been an increase in the number of reports of patients who have experienced the development of autoimmune neurological disorders. It is assumed that such an increase in the incidence rate may occur due to an abnormal immune-mediated response of the body to the pathogenic impact of SARS-CoV-2. This article discusses the possibility of the influence of SARS-CoV-2 on the onset and exacerbation of the course of autoimmune neurological disorders, possible pathogenetic factors and mechanisms, and analyzes the features of the clinical picture and therapy. The article includes foreign and Russian scientific data and clinical observations of cases of Guillain-Barré syndrome, multiple sclerosis, acute disseminated encephalomyelitis, myasthenia gravis and other autoimmune diseases that have changed their typical course on the background of COVID-19.